Oxidase Mimic Graphdiyne for Efficient Superoxide Generation in Wide pH Ranges. (16th November 2021) - Gu, Yu; Fan, Cunxia; Hao, Xijuan; Hu, Fangxin; Zhang, Chunmei; Yang, Hongbin; Li, Chang‐Ming; Guo, Chunxian
Abstract: Great effort has been made in exploring techniques and catalysts for O2 − production but they always work efficiently in either acidic or base environment. Presented here is the design of a unique oxidase mimic catalyst comprising self‐assembled hemin molecules on graphdiyne (hemin/GDY) for efficient O 2− generation in wide pH ranges. Hemin molecules anchor uniformly across the carbon frame of GDY to enable atomic distribution of the active metal sites, delivering a O2 − production rate of 35.7 and 2.3 times than that of hemin and hemin/graphene, respectively. In particular, hemin/GDY can efficiently produce O2 − in acidic, alkaline, and neutral environments, delivering a wide pH behavior. Its oxidase mimic ability is demonstrated for sensing glutathione molecules in cell assays, exhibiting high selectivity, long linear range. This work opens a promising design strategy toward efficient oxidase mimic catalysts for various applications. Abstract : The oxidase mimic of hemin/graphdiyne (GDY) can produce O2 − with high intensity in acidic, alkaline, and neutral environments, and the strength of O2 − increases with the increase in pH value. The material can realize high‐performance glutathione sensing in cell lysate.